Myanmar Monthly Food Price Report – December 2025 - Htar, May Thet; Minten, Bart; Masias, Ian (International Food Policy Research Institute, 2026)
Rice prices declined sharply in December 2025 nationally, falling by 20 percent year-on-year and 5 percent month-on-month. These declines were driven by falling international prices and increased market supply from the monsoon harvest. All states and regions saw stable or declining prices month-on-month, with the largest drops observed in major rice-producing regions such as Ayeyarwady (30 percent) and Sagaing (19 percent). While these trends benefit consumers, they raise concerns for paddy producers, especially in light of rising agricultural input costs. Prices of pulses diverged. Green gram prices rose sharply year-on-year (21 percent), supported by export demand following China’s decision to ease its temporary suspension. In contrast, black gram, chickpea, and pigeon pea prices remained well below last year’s levels, reflecting weak demand from India. Maize prices also declined year-on-year (6.5 percent). Animal-sourced food prices surged over the past year, led by mutton (up 58 percent), due to lower production, while fish prices rose amid strong export demand. Multiple risks lie ahead, including weak international agricultural commodity prices, ongoing conflict, export quality concerns, import restrictions affecting livestock production, border trade and regional policy changes, and policy uncertainty, all of which may undermine agricultural incentives, farm incomes, and food security.